Ghosts. Season three [videorecording (DVD)] - Baynton, Mathew, 1980-; Farnaby, Simon; Howe-Douglas, Martha, 1980-; Howick, Jim; Rickard, Laurence, 1975-; Willbond, Ben, 1973- (BBC Studios, 2022)
Alison and Mike are working hard to bring their new 'guest house' plans to fruition, when the peace is disrupted by an unexpected visitor who arrives with a life-changing revelation. Alison questions everything she thought she knew, and the ghosts react with varying degrees of fear, mistrust, and in some cases, delight. Meanwhile, Mike is more intent than ever to put Button House on the map while trying to hold onto his day job.